PENGARUH SENAM OTAK TERHADAP FUNGSI KOGNITIF DAN KUALITAS TIDUR PADA LANSIA DI PUSKESMAS RANTANG MEDAN - Amila Amila; Henny Syapitri (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Getting old is the process of the changing or phisical appearance and biological decreasing that cause the creasing of sleeping quality and cognitive function to elderly. Brain gym is one of the non pharmacological therapies to stimulate the brain and can fix the nerve position and blood flow, so it can increase the relaxation for the elderly to help sleeping quality and cognitive function. The purpose of this study is to find out the effect of brain gym to the cognitive function and sleeping quality for the elderly in Public Health Centre Rantang Medan. The study design is quasi eksperimental with the approach one group pre and post test design. The sampling method is purposive sampling with 21 elderly. The results of the study show that 67% of the respondents have light cognitive problem and 66,7% have bad sleeping problem after doing brain gym. The t test paired (p<0.05) shows that there is effect of brain gym to the elderly cognitif function and mc nemar (p>0,05) shows that there is no effect of brain gym to the sleeping quality. It is suggested to the public health centre to apply brain gym exercise to the elderly to increse cognitive function and also apply other therapies like aerobic to increase sleeping quality.